Preparation of Multicolor Photoluminescent Carbon Dots by Tuning Surface States - Kai Jiang; Xiangyu Feng; Xiaolu Gao; Yuhui Wang; Congzhong Cai; Zhongjun Li; Hengwei Lin (Nanomaterials, 2019)
The achievements of multicolor photoluminescent (PL)-emissive carbon dots (CDs), particularly red to near infrared (NIR), are critical for their applications in optoelectronic devices and bioimaging, but it still faces great challenges to date. In this study, PL emission red-shifts were observed when tartaric acid (TA) was added into m-phenylenediamine (mPD) or o-phenylenediamine (oPD) solutions as carbon sources to prepare CDs, i.e., from blue to green for mPD and from yellow-green to red for oPD. Morphology and structure analyses revealed that the increased surface oxidation and carboxylation were responsible for the red-shifts of emission, indicating that TA played a key role in tuning the surface state of CDs. These factors could be employed as effective strategies to adjust PL emissions of CDs. Consequently, multicolor PL CDs (i.e., blue-, green-, yellow-green- and red-emissive CDs) can be facilely prepared using mPD and oPD in the absence and presence of TA. Particularly, the obtained red-emissive CDs showed a high PL quantum yield up to 22.0% and an emission covering red to NIR regions, demonstrating great potentials in optoelectronic devices and bioimaging. Moreover, multicolor phosphors were further prepared by mixing corresponding CDs with polyvinylpyrrolidone (PVP), among which the blue, green, and red ones could serve as three primary color phosphors for fabricating multicolor and white light-emitting diodes (LEDs). The white LED was measured to show a Commission Internationale de L’Eclairage (CIE) 1931 chromaticity coordinate of (0.34, 0.32), a high color rendering index (CRI) of 89, and a correlated color temperature (CCT) of 5850 K, representing one of the best performances of white LEDs based on CDs.